Strengthening teacher competence through joyful learning and innovative learning media training - Ghozali Rusyid Affandi; Fika Megawati; Nurfi Laili; Cholichul Hadi; Nur Ainy Fardana Nawangsari; Noer Maunatur Rohmah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
A needs assessment at Muhammadiyah Middle School 9 Tanggulangin revealed that teachers struggle with creating interactive learning environments and developing innovative teaching materials. To address these challenges, a training program was conducted to enhance teachers' pedagogical skills, creativity, and motivation. The program consisted of two key activities: joyful learning training and training in the development of creative and innovative learning media. The process included several stages: preparation (needs assessment, program design, material development, and pre-test), implementation (intensive training on joyful learning and innovative media development), and evaluation. The training involved 12 teachers (4 men and 8 women). The results showed significant improvements in teachers' understanding of joyful learning concepts and their ability to create creative and innovative learning materials. This program highlights the importance of adopting innovative and enjoyable teaching strategies to enhance teacher competence and improve student learning experiences. The initiative demonstrated that targeted training could effectively address the challenges teachers face, leading to better educational outcomes.